Website-Based Learning Media to Improve Elementary School Students’ Reproductive Health Literacy - Mahiroh, Febby Faza; Suryanti; Azizah, Utiya (Universitas Pendidikan Ganesha, 2024)
The significance of reproductive health literacy includes being able to complete every individual’s reproductive rights independently in making health decisions, improving empowerment to fulfill rights and obligations, and being fully accountable for the reproductive process to attain health. The present study aims to analyze the validity, practicability, and effectiveness of website learning medium in increasing reproductive health literacy. This study included 32 class VI elementary school students in the treatment group and 32 students in the control group. The development model employed four-dimensional. Data collection techniques by means of observation, questionnaires and written tests. The data were analyzed by descriptive quantitative. The media validation results yielded a 4 with a very valid category. On the practicality of the media, it was obtained 93% in the learning implementation process and students’ responses to the media with a score of 93% in the very practical category. The students’ learning outcomes increased with an average of 83.7 with an N-Gain value of 0,735 ≥ 0.3 in the high category. Thus, website-based learning media is declared feasible for increasing reproductive health literacy.